First Step in the Reaction of Zerovalent Iron with Water - Karlický, František; Otyepka, Michal (Journal of chemical theory and computation, 2011)
Here we present a comprehensive quantum chemical study of the simplest model system for the reactions of nanoscale zerovalent iron, i.e., the gas-phase reaction of an iron atom with water, to identify a theoretical method that provides reasonably accurate geometries and thermochemical data for selected iron compounds along the reaction path (Fe, FeO, HFeOH, Fe(OH)2). The energies of selected stationary points on the ground electronic potential energy surface were systematically studied using HF and post-HF methods (MP2, MP3, MP4, CCSD, CCSD(T), CASSCF, MRCI) and selected DFT functionals (B3LYP, B97-1, BPW91, M06, M06-HF, M06-L, M06-2X and MPW1K) using various basis sets up to the complete basis set. Scalar relativistic effects were modeled using the Douglas-Kroll-Hess Hamiltonian up to the fourth order, and the effects of valence plus outer-core electronic correlation were also evaluated. The calculations showed that (i) dynamic electron correlation is crucial for accurate modeling of the reactions in question, (ii) the PES around the stationary points along the reaction path is rather flat, (iii) the single-point energies calculated at the CCSD(T)/CBS level are in reasonably good agreement with experimental measurements, (iv) it is difficult to interpret DFT energies in the absence of benchmarking against experimental data or results obtained at a level of theory that is known to accurately reproduce experimental results, (v) relativistic effects are relatively modest in this system but should be included if chemical accuracy is desired, and (vi) careful analysis of the multireference character of the system and potential spin contamination is important. The CCSD(T)-3s3p-DKH2/CBS method can be considered the gold standard for this reaction because calculations at this level are in good agreement with experimental atomic excitation energies and thermochemical data. The gas-phase activation energy of the reaction between Fe and H2O is 23.6 kcal/mol including the ZPVE correction (ΔG(‡)298K = 29.2 kcal/mol), and HFeOH is a stable intermediate lying -31.2 kcal/mol below the reactants (ΔG298K = -25.4 kcal/mol).